Efficacy of salvage therapies for advanced acral melanoma after anti-PD-1 monotherapy failure: a multicenter retrospective study of 108 Japanese patients - Mori, Tatsuhiko; Namikawa, Kenjiro; Yamazaki, Naoya; Kiniwa, Yukiko; Yamasaki, Osamu; Yoshikawa, Shusuke; Inozume, Takashi; Kato, Hiroshi; Nakai, Yasuo; Fukushima, Satoshi; Takenouchi, Tatsuya; Maekawa, Takeo; et al. (Frontiers in Medicine, 2023)
Background Anti-programmed cell death protein 1 (PD-1) monotherapy is one of the standard systemic therapies for advanced melanoma; however, the efficacy of salvage systemic therapies after PD-1 monotherapy failure (PD-1 MF), particularly in acral melanoma (AM), the main clinical melanoma type in Japanese patients, is unclear. This study aimed to investigate the efficacy of salvage systemic therapies in Japanese patients with AM after PD-1 MF. Patients and methods The study included 108 patients with advanced AM (palm and sole, 72; nail apparatus, 36) who underwent salvage systemic therapy at 24 Japanese institutions. We mainly assessed the objective response rate (ORR), progression-free survival (PFS), and overall survival (OS). Results Thirty-six (33%) patients received ipilimumab, 23 (21%) received nivolumab and ipilimumab (nivo/ipi), 10 (9%) received cytotoxic chemotherapy, 4 (4%) received BRAF and MEK inhibitors (BRAFi/MEKi), and the remaining 35 (32%) continued with PD-1 monotherapy after disease progression. The ORRs in the ipilimumab, nivo/ipi, cytotoxic chemotherapy, and BRAFi/MEKi groups were 8, 17, 0, and 100%, respectively. The nivo/ipi group showed the longest OS (median, 18.9 months); however, differences in ORR, PFS, and OS between the groups were insignificant. The OS in the nivo/ipi group was higher in the palm and sole groups than in the nail apparatus group (median: not reached vs. 8.7 months, p < 0.001). Cox multivariate analysis demonstrated that nail apparatus melanoma independently predicted unfavorable PFS and OS (p = 0.006 and 0.001). The total OS (from PD-1 monotherapy initiation to death/last follow-up) was insignificant between the groups. Conclusion Nivo/ipi was not more effective than cytotoxic chemotherapy and ipilimumab after PD-1 MF in patients with advanced AM. The prognosis after PD-1 MF would be poorer for nail apparatus melanoma than for palm and sole melanoma.